2011
DOI: 10.1007/s00227-010-1620-4
|View full text |Cite
|
Sign up to set email alerts
|

Archival tagging of subadult and adult common thresher sharks (Alopias vulpinus) off the coast of southern California

Abstract: The common thresher shark (Alopias vulpinus) is a secondary target species of the California drift gillnet fishery (CA-DGN) and supports a growing recreational fishery in California waters. This study used archival tags to examine the movement patterns and habitat preferences of common threshers of the size range captured in the CA-DGN (>120 cm fork length). Depth and temperature-logging archival tags were deployed on 57 subadult and adult common threshers in the Southern California Bight. Tags from five indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…1). The horizontal movements recorded in this study are much greater than those reported for several other temperate and tropical reef fishes (Holland et al, 1996;Lowe et al, 2003;Wetherbee et al, 2004;Topping et al, 2005;Bellquist et al, 2008) and more similar to those described for pelagic species (Carey & Scharold, 1990;Holland et al, 1990b;Sepulveda et al, 2004;Cartamil et al, 2011). Due to the short duration and relatively unpredictable and extensive nature of the movements reported in this study, calculations of home range and investigations of site fidelity were not feasible.…”
Section: Horizontal Movementssupporting
confidence: 48%
“…1). The horizontal movements recorded in this study are much greater than those reported for several other temperate and tropical reef fishes (Holland et al, 1996;Lowe et al, 2003;Wetherbee et al, 2004;Topping et al, 2005;Bellquist et al, 2008) and more similar to those described for pelagic species (Carey & Scharold, 1990;Holland et al, 1990b;Sepulveda et al, 2004;Cartamil et al, 2011). Due to the short duration and relatively unpredictable and extensive nature of the movements reported in this study, calculations of home range and investigations of site fidelity were not feasible.…”
Section: Horizontal Movementssupporting
confidence: 48%
“…Cephalopods as a group are abundant in the water column and it is not surprising that they are consumed by top predators, shown in this study. Each shark and billfish species has a different vertical distribution, the habitat of the species of the G Model genus Sphyrna ranges from close to the water surface and extends down to a depth of 900 m (Bassuno et al, 2011;Hoffmayer et al, 2013), Alopias reaches a depth less than 500 m (Weng and Block, 2004;Cartamil et al, 2011) and P. glauca is found as deep as 1000 m (Vögler et al, 2012). As a result of these predatorís vertical distribution, there is exploitation of a wide range of cephalopod prey as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that oceanic whitetips dive to feed on mesopelagic cephalopods just as short-finned pilot whales ( Globicephala macrorhynchus ) do [39]–[40], since oceanic whitetips have been reported to associate with these cetaceans [41]. The “fast descent, slow ascent” dive profile observed in oceanic whitetips also occurs in other pelagic sharks and is postulated to be prey searching behavior [42][43]. All of these factors suggest that mesopelagic diving by oceanic whitetips is most likely related to foraging.…”
Section: Discussionmentioning
confidence: 99%